Representations of a president through the state of the nation addresses (2001-2009) - Maximo, Alexander Corpuz (2010)
The study investigated the representations of Gloria-Macapagal Arroyo (GMA) in the State of the Nation Addresses (SONA) she delivered from 2001-2009. The study examined the texts through the lense of Norman Fairclough's Critical Discourse Analysis (CDA). The study also employed corpus-assisted techniques in an effort to synergize qualitative and quantitative methods. By focusing on the 'pronoun' I and the process types with which the pronoun occurs, the study was able to determine the quality of GMA's representations. The findings indicated that GMA was generally positively represented through actions associated to her role as president. The changes in frequencies and the qualities of representations through the nine SONAs also appeared to be affected by the historical contexts of the SONAs. Thus, the study enforces the fundamental claim of CDA of social determinants shaping the discourse.
Thesis (M.A. English Studies : Language)--University of the Philippines Diliman.
Keywords: Macapagal-Arroyo, Gloria -- 1947-.; Critical discourse analysis -- Politics and government -- Philippines